Language and acknowledgment: a heideggerian perspective - Rocha de la Torre, Alfredo (Estudios de Filosofía, 2010)
The thesis of this article expounds that Heideggerian Philosophy enables a meditation on the experience of the acknowledgment of the other. After questioning some of the criticisms directed to Heidegger due to his emphasis on the ontological scope, the sense of the concept of acknowledgment concept and its nexus with the notion of nearness is approached, to end up with the identification of nearness with language. This identfication will give to the experience of acknowledgment its ontic-ontological character that will allow the understanding of its "essence". The question on the condition of possibility of acknowledgment will lead to the concept of "Vorausahnung", not treated by Heidegger but made possible by his philosophizing. It concludes with the conception of acknowledgment as a structural condition of human existence.